2018
DOI: 10.1186/s12868-018-0436-x
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of thyroxine may predict a favorable response to donepezil treatment in patients with Alzheimer disease: a prospective, case–control study

Abstract: BackgroundCholinergic hypothesis has been advanced as an etiology of Alzheimer disease (AD) on the basis of the presynaptic deficit found in the diseased brains, and cholinesterase inhibitors (ChEIs) are the treatment of choice for these patients. However, only about half of treatment efficacy was found. Because increasing evidence supports an extensive interrelationship between thyroid hormones (THs), cortisol level and the cholinergic system, the aim of the present study was to evaluate thyroid function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…A study conducted by Yu San Chang et al 2018 has shown that the responders had a higher level of T4 than the nonresponders, followed by a significant reduction after donepezil treatment. These results indicate that relatively higher levels of T4 may predict a favorable response to donepezil treatment [3]. In our study, no beneficial effects of the donepezil and Vit B 12 therapy were observed on the thyroid profile in a duration of 6 months.…”
Section: Resultscontrasting
confidence: 40%
See 1 more Smart Citation
“…A study conducted by Yu San Chang et al 2018 has shown that the responders had a higher level of T4 than the nonresponders, followed by a significant reduction after donepezil treatment. These results indicate that relatively higher levels of T4 may predict a favorable response to donepezil treatment [3]. In our study, no beneficial effects of the donepezil and Vit B 12 therapy were observed on the thyroid profile in a duration of 6 months.…”
Section: Resultscontrasting
confidence: 40%
“…The most widely recognized association between endocrine and cognitive functions involves the thyroid hormone supported by increasing pieces of evidence about an extensive inter-relationship between thyroid hormones and the cholinergic system. Thyroxin (T4) has been shown to modulate choline acetyltransferase activity, and triiodothyronine (T3) has been shown to negatively regulate the expression of amyloid precursor protein (APP) in the brain [3,4]. Although the progressive cognitive decline is a critical clinical feature of AD, mood disturbance and behavioral symptoms are very common in patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, donepezil dose-dependently increased whole-body cortisol levels in zebrafish (Figure 2), consistent with its putative acute anxiogenic-like behavioral effects described here (Figure 1). However, while AD patients demonstrate elevated cortisol, donepezil treatment is ineffective (Furiya et al, 2018; San Chang et al, 2018), as is another AChE inhibitor, pyridostigmine, unaltering adrenocorticotropin and cortisol in men (Freeman et al, 1990), or corticosterone in rodents (Kant et al, 2001). Importantly, elevated whole-body cortisol levels have been linked to increased anxiety-like behaviors in various zebrafish models (Demin et al, 2020; Egan et al, 2009; Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, reducing the production of acetylcholine, as a neurotransmitter, leads to AD. Therefore, cholinesterase inhibitors (ChEIs) can be considered as potential targets for the treatment of AD 3 . Donepezil HCl (DH) is one of the ChEIs developed for AD treatment 4 .…”
Section: Introductionmentioning
confidence: 99%